Increasing the Knowledge and Skills of Cadres and Mothers of Toddlers in Utilizing Local Food in Pilolodaa Village - Misnati, Misnati; Setiawan, Denny Indra; Amalia, Mutia Reski (Jurnal Abmas Negeri (JAGRI), 2025)
Stunting is a national problem that has not been solved until now. This problem requires handling that involves all health professions and health education. Pilolodaa Village is one of the loci of stunting in the Gorontalo City area. The results of PPGBM data from posyandu data from January to June 2022 show that Pilolodaa Village has 30 stunting cases (TB/U) of toddlers. Based on data from nutritionists at the Pilolodaa Health Center, there are still mothers under five who lack knowledge about stunting prevention and lack skills to use local food to make highly nutritious food. The activity aimed to improve the knowledge and skills of mothers and cadres in utilizing local food to increase family independence in preventing stunting. Counseling was given to 30 mothers of toddlers and 5 posyandu cadres. The method implemented was to provide counseling and education on stunting prevention and demonstrations of making local food-based foods using leaflet media and videos of product making as well as direct demonstrations. The results of the activity showed an increase in the knowledge of posyandu cadres and mothers under five about stunting prevention by 65% as measured from pre-post tests and an increase in the skills of posyandu cadres and mothers of toddlers in processing local food-based food by 100%. As a result of the Community Service activities conducted in Pilolodaa Village, West Kota District, Gorontalo City, the knowledge of cadres and mothers of toddlers about stunting increased by 65%.